IMPACT OF BUYER’S LENIENT POLICY OF RETURN AND TRUST ON INTERNET PURCHASE DECISION IN SUPPLY CHAIN SECTOR OF PAKISTAN - Ansari, Muhammad Ammad; Zaman, Sohaib Uz (Asian Finance & Banking Review, 2021)
This article aims to investigate the factors that impact the internet purchase decision in supply chain sector of Pakistan because our mode of purchasing has been changed dramatically as a result of the Internet. An increasing number of individuals prefer online mode of shopping rather than in physical stores. Despite of these benefits there possess some cons of online purchasing like complicated returns, difficult websites, no sales assistance and lack of trust. In this article, impact of two independent variable i.e., lenient policy of return of buyer and trust of buyer was analyzed against the dependent variable internet decision of purchase. A questionnaire of 21 questions was prepared. Data of 100 respondents was collected from buyers of Karachi. Reliability Analysis, ANOVA and regression analysis are performed using SPSS tool to find the results. Study concluded that lenient policy of return of buyer and trust of buyer has positive association with internet decision of purchase in Pakistan which means when buyers are provided with lenient policies for the return of goods for any reason and their trust in seller increases it will impact the decision of purchase positively. Thus, it will be beneficial in terms of chasing market competition and generating higher returns.